An e-commerce implementation framework for Nordin Batik and Craft Sdn Bhd / Nor Hisham Ismail - Ismail, Nor Hisham (2011)
Nowadays, the internet becomes a well known medium for business to improve marketing and revenues. At the same time, the management of selected batik company in this research was inspired to adopt e-commerce in business to expanding product promotion, marketing and gain more revenue at low cost. Thus, the batik company needs an effective e commerce solution tool to help an implementation process. Hence, the research purpose was to develop an e-commerce implementation framework. A conceptual framework was designed based on literature review of multiple sources such as books, e-books, journals, articles, e-articles, thesis, government documents and United Nation documents, which are available either online or offline. The synthesis of existing models, frameworks and related theories was made to measure and discuss all elements in previous theories but only elements that reflected managerial and technological aspects were adapted for the purpose of this research. Case study with an expert interview data collection technique was used. Other sources used for data collection were from documents, images, videos, observation, interviews recorded audio and research diary. Collected data was analyzed using Nvivo, a computer aided qualitative data analysis (CAQDAS). The Nvivo assisted the researcher in data management and gave researcher a chance to control the overloaded qualitative data. The Nvivo based qualitative data analysis started with creating free nodes in coding phase, the categories created and then the themes. All these used to easily manage data and gave broader view and prespective for delivering better results as reported in the findings section. The finding shows that managerial aspect and technological aspect are both important for e commerce implementation. The most important factor in managerial were the top management support, manager attitude and characteristics altogether with top management intention, commitment and continuing involvement in implementation which are actually reflected to readiness for e-commerce. Other factors whether the internal factors such as infrastructure, facilities, managerial, and technology or external factors such as enabling environment and government were less important compared to managerial and technological aspects discussed. At the same time, a time factor found has a controller effect to the implementation process. However, time factor effect is fully depending on managerial decision. The researcher suggests that implementation must goes on phased approach and do not employed the framework simultaneously. The findings and expert suggestions were used to enhance the design of e-commerce implementation conceptual framework. The enhanced framework is produced based on conceptual framework but with additional improvement from research analysis and findings which contains an expert's opinion supported with secondary data. The enhanced framework was compact and comprehensive but simple and easy to follow with its guidelines attached together.